An Ethnographic Study on the Use of English among Students at Kolej Universiti Islam Malaysia (Malaysian Journal of Learning and Instruction, 2005)
This article is based on a four-week ethnographic study of a discourse community i.e. first and second year students of Kolej Universiti Islam Malaysia (KUZM). The researchers believe that the ethnographic approach could help provide valuable insights that would indirectly help them t o understand the use of the English Language by the discourse community. Tools of inquiry such as non-participant observations, specialist informants, interviews, and questionnaire as well as a re-examination of relevant documents were employed for data gathering purposes. The findings of this study indicate that English Language use at KUIM is not only dependent on the conventions laid down by the university but also by the discourse community. The paper discusses the implications of the findings on producing and designing meaningful teaching-learning material for the discourse community.